An overview of grid associated wind energy conversion systems control strategies - Ranjan Mahapatra, Tapas; Chaudhary, Satis (International Journal of Psychosocial Rehabilitation, 2025)
Wind vitality transformation system (WECS)” is assimilate through utility framework by means of “power electronic converters” which assumes a significant job in combination with wind control interested in the electric network. The primary power eminence unsettling influences because of incorporation of “WECS” to matrix are variety on power & sounds. To keep up matrix management & to preserve all out symphonies twisting (THD) inside operational breaking points, suitable control plans are essential on behalf of said network flank converter. Primary target of framework cross controller that controls said power conveyed to said matrix, network management, headed for hoard great capacity to lattice & headed for meeting lattice code consistence. In particular work governor plans utilized in framework interfaced wind vitality change framework aimed at generator part & network part wise converter monitor, are assessed completely. The work exhibits a relative investigation by rotor flux situated govern and “direct torque control (DTC)” methods connected at generator part converter about “permanent magnet synchronous generator” (PMSG) driving by wind turbine machine. For framework part converter, different govern plans that grown for the most part dependent at “voltage organised control (VOC)” or on “direct power control (DPC)”. The exhibition by VOC put together monitor framework fundamentally depends with respect to strategy connected that controls current. A near report performed among them & analysing are arranged. Reconciliation prerequisites by wind turbine from framework, matrix management & necessity of checking unit are likewise talked about.